Presentation of aggressive high-grade B cell lymphoma as venous thromboembolism - Ali, Shahnila; Hussain, Taarif (International Journal of Research in Medical Sciences, 2017)
Patient with no known past medical history who came to United States few years back and no established PCP noticed right groin swelling and discomfort for 3 days. In addition to right groin swelling and discomfort, she also noticed fatigue especially at work. Due to progressive symptomatology, she seeked help at urgent care. On physical examination performed by urgent care doctor, patient found to have inguinal lymphadenopathy, which led to general surgery referral and subsequent lymph node biopsy a day afterwards. Curious surgeon followed pathology report, which turned out to be Burkitt’s lymphoma. Subsequently, surgeon referred for survey which included CT scans abdomen and pelvis with contrast. Radiologist reading imaging called patent to go to ED STAT as she found massive B/L pulmonary embolism in main pulmonary arteries incidently. Other findings included lymphadenopathy in the right inguinal, right pelvic and peri aortic locations. Mildly enlarged left pelvic lymph node. No lymphadenopathy in the chest. Patient was initiated immediately on heparin infusion on presentation to ED. Oncology consulted and ordered additional studies including ECHO. Patient received bone marrow biopsy and lumbar puncture as well. She was initiated on standard chemotherapy R-EPOCH regimen. Patient also received allopurinol entecavir and bactrim Subsequently, bone marrow biopsy results showed high grade B cell Lymphoma. Staging bone marrow negative. LP showed normal protein, borderline elevation of glucose, flow cytometry and cytology negative for involvement. C-myc translocation, phenotype of Burkitt’s but with lower Ki67. Sites of disease included massive right inguinal adenopathy, peri aortic and left pelvic adenopathy. Patient was followed during the hospital course and had excellent recovery. Symptomatically, she no longer felt fatigued and leg swelling / groin mass significantly improved at time of discharge. She was discharged in stable condition with outpatient follow up with oncology. Aggressive High Grade B cell Lymphoma may present with venous thromboembolism and due to aggressive nature of lymphoma, venous thromboembolism can pose/present with significant clot burden before being diagnosed Lymphoma should be considered as a causative disease in a patient even adult with venous thromboembolism Aggressive evaluation and prompt treatment is needed for good results and recovery